Refractive index sensor using microfiber-based Mach-Zehnder interferometer - Sun, Qizhen (2013)
A simple and robust refractive index (RI) sensor based on a Mach–Zehnder interferometer has been demonstrated. A section of optical microfiber drawn from silica fiber is employed as the sensing arm. Because of the evanescent field, a slight change of the ambient RI will lead to the variation of the microfiber propagation constant, which will further change the optical length. In order to compensate the variation of the optical length difference, a tunable optical delay line (ODL) is inserted into the other arm. By measuring the delay of the ODL, the ambient RI can be simply demodulated. A high RI sensitivity of about 7159  μm/refractive index unit is achieved at microfiber diameter of 2.0 μm.